Anticoagulant and antiplatelet treatment in cancer patients with thrombocytopenia. Issue 191 (July 2020) - Leader, Avi; Gurevich-Shapiro, Anna; Spectre, Galia
Abstract : A B S T R A C T Antithrombotic therapy (anticoagulation or antiplatelet therapy) is frequently prescribed in cancer patients for prior or new indications such as venous thromboembolism, secondary prevention of arterial thrombosis or atrial fibrillation. Therefore, it is not uncommon for thrombocytopenic cancer patients to have an indication for antithrombotic therapy. Thrombocytopenia does not reduce the risk of recurrent thrombosis. The bleeding risk with anticoagulation appears to increase when platelets are < 50 × 10 9 /L, but individual platelet counts are poor predictors of bleeding. Management options when platelets are < 50 × 10 9 /L include no change, temporarily withholding antithrombotic therapy, reducing dose, changing the regimen, and increasing the platelet transfusion threshold. There are currently no data on use of direct oral anticoagulants when platelets are below 50 × 10 9 /L, and there is reason in restricting their use. Little is known on antiplatelet therapy in this setting, although recent data suggest the prognostic importance and apparent safety of aspirin in acute myocardial infarction and thrombocytopenia. This paper will review the evidence, guidelines, current practice and ongoing studies on anticoagulation and antiplatelet therapy in thrombocytopenic patients with cancer.